ANALISIS KONSEPTUAL PENGARUH TRAFIK BUSY HOUR TERHADAP PERFORMA JARINGAN SELULER - Ervin Nawal Andra; Yulindon Yulindon (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid growth of mobile data traffic in cellular networks has created significant challenges in maintaining network performance, particularly during peak usage periods known as busy hour. During these periods, high user density leads to increased traffic load, resulting in network congestion and degradation of key performance indicators such as throughput, latency, jitter, and packet loss. This study aims to analyze conceptually the impact of busy hour traffic on cellular network performance through a structured literature review approach. The method involves collecting and synthesizing recent studies from reputable journals to identify patterns and relationships between traffic load and network performance parameters. The results indicate that increased traffic during busy hour consistently causes resource contention, leading to decreased throughput and increased latency, jitter, and packet loss. Furthermore, this study reveals that most existing research is empirical and case-specific, lacking an integrated conceptual framework. Therefore, this research contributes by providing a comprehensive conceptual understanding of the causal relationship between busy hour traffic and cellular network performance degradation, which can support future research and network optimization strategies.